Levator ani trauma and pelvic organ prolapse – a comparison of three translabial ultrasound scoring systems. (15th October 2016) - Trutnovsky, Gerda; Kamisan Atan, Ixora; Ulrich, Daniela; Martin, Andrew; Dietz, Hans P.
Abstract: Introduction: The study aimed to analyze the relation between the degree of puborectalis muscle trauma and subjective symptoms and objective findings of pelvic organ prolapse (POP), comparing two continuous scoring systems with a discrete scoring system for translabial ultrasound imaging. Material and methods: In this retrospective observational study the records of patients attending a tertiary urogynecological unit between January 2012 and December 2014 were analyzed. POP assessment included a standardized interview, clinical examination using Pelvic Organ Prolapse Quantification and four‐dimensional translabial ultrasound. Puborectalis muscle trauma was assessed with tomographic ultrasound imaging using two continuous scoring systems and a previously established discrete system. Receiver operating characteristics and adjusted odds ratios were used for comparison of scoring systems in predicting symptoms and signs of POP. Results: Of 1258 women analyzed, 52.6% complained of prolapse symptoms. On ultrasound imaging, 65.7% of women had sonographically significant POP. Complete avulsion was diagnosed in 25.3% of women, being unilateral in 13.9% and bilateral in 11.4%. A maximum score in the 6‐point and the 12‐point tomographic ultrasound imaging scale increased the odds for a diagnosis of any significant POP on ultrasound by 4.4 and 4.8 times, respectively, compared with 4.6 times for the discrete diagnosis of bilateral avulsion. For all avulsion scoring systems the relation was strongest for cystocele and uterine prolapse. Conclusions: A continuous avulsion scoring system based on tomographic findings does not provide superior performance for the prediction of subjective symptoms and objective findings of prolapse compared with a discrete diagnostic system of unilateral or bilateral avulsion.